CHROMOSOME NUMBER AND TIME PERIOD OF MITOTIC CYCLE OF FESTIVAL AND CALIFORNICA STRAWBERRY CULTIVARS (Fragaria x ananassa AND Fragaria vesca) - Aristya, Ganies Riza; Alyza, Rezika; Khoiroh, Rosyidatul; Daryono, Budi Setiadi (2013)
The cultivated strawberries, Fragaria x ananassa and Fragaria vesca, are the most economically-important softfruit species. F x ananassa and F vesca, both diploid (2n=2x=14) relatives of the commercial octoploid strawberry, are an attractive model for functional genomics research in Rosaceae. Its small genome size, short reproductive cycle, and facile vegetative and seed propagation make F. x annassa and F.vesca a promising candidates for forward and reverse genetics experiments. In order to determine their genetic differences in more detail, chromosome characterization of the two strawberry cultivars was investigated. A method used for chromosome slides in this research was a squash method with modification in pre-treatment. The result showed Fragaria x ananassa had (2n = 4x = 28) chromosome number is 28 and Fragaria vesca had (2n = 2x = 14) chromosome number is 14. The time of mitotic that both strawberry cultivars was similar at 7 to 8.30 am. In addition, mixoploid cells were found in both strawberry cultivar indicating that these cultivars had been treated by mutagenic agents for a breeding program.